DEVELOPMENT OF RELIGIOUS TOLERANCE OF HIGH SCHOOL LEVELS - Eri Nurul Fahmi; Endin Mujahidin; Imas Kania Rahman (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
Religious tolerance of Bogor An-Nur Aliyyah high school students is known that the religious tolerance of students is still low, known to the fact that the majority of students lose their tolerance. Factors that influence this occur because many students are less study and live the concept of tolerance, so that the spirit of tolerance is weakened. In addition, students also lose the spirit of togetherness, and many do not base Pancasila as the basis of the life of the Indonesian people, aka all of them individually, causing intolerance in their lives. This study aims to 1) Analyze the concept of religious tolerance according to Ibnu Taimiyah; 2) Analyzing religious tolerance in An-Nur Aliyyah Bogor high school students, and 3) Developing the development of co-curricular activities in increasing religious tolerance. The research approach used is a content analysis approach. The data source consists of primary data sources consisting of the Book of Tolerance Learning by Ibnu Taimiyah. The results of the study note that 1) Religious tolerance in An-Nur Aliyyah high school students Bogor is known that religious tolerance of students is still low in the level of religious tolerance of students. 2) The concept of religious tolerance according to Ibnu Taimiyah which can be applied as a basic reference for the preparation of co-curricular activities in An-Nur Aliyyah High School Bogor consists of the concept of God as a source of love, the concept of the Prophet Muhammad is a practical example of compassion, the concept of no coercion in religion, the concept of faith and good deeds as the basis of tolerance, the concept of prohibiting spreading hatred, the concept of prohibiting spreading violence, and the concept of prioritizing the way of peace. 3) Development of Co-curricular Activities Program in increasing religious tolerance according to the concept of Ibnu Taimiyah in An-Nur Aliyyah High School Bogor, which is moving towards the existence of thoughts to build religious tolerance, especially in peer tutoring activities, literacy programs of exemplary stories, filling wall magazine content ( mading) schools, visits to orphanages, orphans or visiting street children, campaigns against hoaxes and hate speech, research assignments in the form of papers, and simulations dealing with fights and fights. Keywords: Ibn Taymiyyah, Co-curricular, Religious Tolerance